2009
DOI: 10.1002/zamm.200900366
|View full text |Cite
|
Sign up to set email alerts
|

On some constitutive equations for micropolar plates

Abstract: In this paper we discuss the constitutive relations for micropolar plates recently obtained by Altenbach and Eremeyev. We pay particular attention to their relation for the resultant drilling stress couple and compare it with that used so far in the statically and kinematically exact nonlinear six‐parameter shell theory. Using the results of Altenbach and Eremeyev, we present bounds on values of the constitutive parameter αt from the six‐parameter shell theory model. Some representative numerical simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Since the role of a t was not understood within the general sixfield theory of elastic shells, Chróścielewski et al (2004) and Chróścielewski and Witkowski (2010a) performed extensive numerical tests in order to analyse how values of a t influence the static and dynamic behaviour of several regular and irregular elastic shell structures within the linear and geometrically non-linear range of deformation. It was found, in particular, that when a t < 1 the results were practically insensitive to its numerical value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the role of a t was not understood within the general sixfield theory of elastic shells, Chróścielewski et al (2004) and Chróścielewski and Witkowski (2010a) performed extensive numerical tests in order to analyse how values of a t influence the static and dynamic behaviour of several regular and irregular elastic shell structures within the linear and geometrically non-linear range of deformation. It was found, in particular, that when a t < 1 the results were practically insensitive to its numerical value.…”
Section: Discussionmentioning
confidence: 99%
“…Altenbach and Eremeyev (2009) suggested that the constitutive relations used in the general shell theory may be viewed as equivalent to their material law proposed for the Cosserat plates. In particular, Chróścielewski and Witkowski (2010a) derived from results of Altenbach and Eremeyev (2009) the analytic formula for a t valid in the case of non-polar material:…”
Section: ð1:23þmentioning
confidence: 99%
“…The boundary-value problem (6), (7), (15), and (16) supplemented by the constitutive equation (17) describes finite deformations of the isotropic micropolar shell. Numerical solutions of few examples are presented in [16][17][18][19] among others.…”
Section: Dynamics and Statics Of Micropolar Plates And Shellsmentioning
confidence: 99%
“…The value α t = 0.7 was proposed by Pietraszkiewicz [48,49], see also [11]. In [10,11,12] the influence of α s and α t on the solution is investigated numerically for several boundary-value problems.…”
Section: On the Constitutive Equations Of Micropolar Shellsmentioning
confidence: 99%
“…Numerical algorithms for solution of the reduced systems of nonlinear equations. For example, it can be done within the framework of the finite element method, see for example the numerical results in [10,11,12]. 3.…”
Section: Principle Peculiarities Of the Micropolar Shell Theorymentioning
confidence: 99%